Microglial response in triggering receptor expressed on myeloid cells 2 (TREM2) knock-out mice after systemic stimulation with Escherichia coli. (1st November 2022) - Hoogland, Inge C.M.; Yik, Jutka; Westhoff, Dunja; Engelen-Lee, Joo-Yeon; Valls Seron, Merche; Man, Wing-Kit; Houben-Weerts, Judith H.P.M.; Tanck, Michael W.; van Westerloo, David J.; van der Poll, Tom; van Gool, Willem A.; van de Beek, Diederik
Highlights: Loss of function of TREM2 during systemic infection leads to an increased number of microglial cells in thalamus after inoculation . Loss of function of TREM2 during systemic infection does not lead to increased expression of pro-inflammatory genes in the brain. The role of TREM2 in the neuro-inflammatory response following systemic infection appears to be limited in our experiments. Abstract: Background: Systemic infection is an important risk factor for delirium, associated with neurodegeneration and subsequent cognitive impairment in older people. Microglial cell response is a known key player in this process and we hypothesize that the triggering receptor expressed on myeloid cells 2 (TREM2) plays an important role in the regulation of this response. Methods: 8- to 10-week old male wild-type (WT) and TREM2 knock-out ( Trem2 -/- ) mice were intraperitoneally inoculated with live Escherichia coli ( E. coli ) or saline. After inoculation, all mice were treated with ceftriaxone (an antimicrobial drug) at 12 and 24 h and were sacrificed after 2 and 3 days. Microglial response was determined by immunohistochemical staining with an ionized calcium-binding adaptor molecule 1 (Iba-1) antibody and flow cytometry. mRNA expression of pro- and anti-inflammatory mediators was measured to quantify the inflammatory response. Results: We observed increased Iba-1 positive cells number in thalamus of Trem2 -/- mice at 3d after inoculation compared to WT mice (mean 120 cell/mm 2 [SD 8] vs 105 cell/mm 2 [SD 11]; p = 0.03). Flow cytometry showed no differences in forward scatter or expression of CD11b, CD45 and CD14 between WT and Trem2 -/- mice. The brain mRNA expression levels of tumor necrosis factor alpha (TNF-α) of Trem2 -/- mice at 2d were higher compared to WT mice (p = 0.003). Higher mRNA expression of interleukin 1 beta (IL-1β), Iba-1, CD11b and mitogen-activated protein kinase 1 (MAPK-1) was found in brain of WT mice at 2d compared to Trem2 -/- mice (respectively p = 0.02; p = 0.001; p = 0.03 and p = 0.02). In spleen there were no differences in inflammatory mediators, between WT and Trem2 -/- mice. Interpretation: Although the loss of function of TREM2 during systemic infection led to an increased number of activated microglia in the thalamus, we did not observe a consistent increase in expression of inflammatory genes in the brain. The role of TREM2 in the neuro-inflammatory response following systemic infection therefore appears to be limited.